Partial Stenosis and Complete Punctal Closure Following Topical Netarsudil Use for Glaucoma. Issue 11 (6th November 2022) - Rashad, Ramy; Zhu, Catherine; Kupcha, Anna C.; Distefano, Alberto G.; Kefella, Haben; Desai, Manishi A.
Abstract : Purpose: To describe patients who developed partial or complete punctal closure after the use of topical netarsudil in the treatment of glaucoma, with documented reversal of symptoms on drug cessation. Patients and Methods: This is a retrospective, single-center case series including patients treated with topical netarsudil who were documented to have developed punctal disease ipsilateral to the eye(s) being treated. A literature review was also performed to identify other similar reports. Results: A total of 10 patients were included in the study. Six patients developed partial punctal stenosis and 4 patients developed complete closure of the puncta in 1 or both eye(s) ipsilateral to the use of the topical medication. None of the patients developed punctal disease on the non-netarsudil side. The time from initiation of netarsudil to the documentation of punctal disease ranged from 5–32.2 months (18.41±9.94). In the patients with complete punctal closure, discontinuation of the topical medication led to clinical reappearance of the punctal opening, ranging from 31–83 days after drug cessation (45.75±21.57). In 8 cases, discontinuation of netarsudil resulted in improved epiphora and degree of punctal stenosis on clinical examination. Conclusions: The use of topical netarsudil for glaucoma may lead to punctal stenosis and complete punctal closure. These side effects of netarsudil are relevant to therapeutic considerations for glaucoma patients.